Designing Multicolor Dual‐Mode Lanthanide‐Doped NaLuF4/Y2O3 Composites for Advanced Anticounterfeiting. Issue 2 (20th November 2019) - Chen, Xiao; Yao, Weijing; Wang, Qi; Wu, Wei
Abstract: Owing to the large coding capacity and high confidentiality, dual‐mode or multimode anticounterfeiting fluorescent materials are gradually substituting traditional single‐mode fluorescent materials. Herein, a facile hydrothermal method is designed and used to integrate lanthanide ion (Ln 3+ )‐doped NaLuF4 nanoparticles with Y2 O3 ‐based downconversion nanorods, achieving the construction of dual‐mode luminescent composite materials. The excellent optical properties of NaLuF4 /Y2 O3 composites are confirmed by photoluminescence spectroscopy. The composites can be excited by a 980 nm laser to generate bright red, green, and blue colors (corresponding to Er 3+ /Tm 3+ ‐, Yb 3+ /Ho 3+ ‐, and Yb 3+ /Tm 3+ ‐doped NaLuF4, respectively), and turn into dim‐red and green colors under an excitation source of 254 nm. Furthermore, the polyvinyl alcohol (PVA)‐mediated stable fluorescent inks are successfully formulated and then printed onto the paper, aluminum foil, and fabric by low‐cost and simple screen printing techniques to fabricate various anticounterfeiting patterns. Interestingly, the printed patterns are hard to observe under ambient light, enabling the generation of multiple emission color under excitations of 980 and 254 nm. The prepared dual‐mode NaLuF4 /Y2 O3 composite materials with outstanding stability and distinctive multicolor luminescent properties provide low‐cost, highly effective, multilevel protection for genuine products against counterfeit. Abstract : Various lanthanide‐doped NaLuF4 /Y2 O3 nanocomposite materials are designed here for obtaining screen‐printed multicolor dual‐mode fluorescent patterns with large encoding capacity in advanced anticounterfeiting field. The fluorescent composites are fabricated by a facile hydrothermal method and generate multiple emission color under excitations of 980 and 254 nm, which provide low‐cost, highly effective, multilevel protection for genuine products against counterfeit.